Артикуляція етимології поняття сакрального - Патерикіна, В.В. (Культура народов Причерноморья, 2013)
Сакральне виступає метакатегорією культури, бо охоплює всі сфери буття. Незважаючи на
важливість вивчення сакрального, саме поняття має різноманітні тлумачення. Культурологічна думка
виводить етимологію сакрального з різних позицій, залежно від історичного часу та територіального
простору. У латинській, давньогерманській, давньослов’янскій мовах, на санскриті сакральне мало
різні відтінки, починаючи від відповідності Космосу та втілення реальності до визначення стану
відринутого до проклятого.
Ключові слова: сакральне, профанне, культура, священий, ієротопія Сакральное выступает метакатегорией культуры, ибо охватывает все сферы бытия.
Несмотря на важность изучения сакрального, само понятие имеет различные толкования.
Культурологическая мысль выводит этимологию сакрального из разных позиций, в зависимости от
исторического времени и территориального пространства. В латинском, древнегерманском,
древнеславянском, на санскритском языках сакральное имело различные оттенки, начиная от
соответствия Космосу и воплощения реальности до обозначения состояния отверженного и
проклятого.
Ключевые слова: сакральное, профанное, культура, священный, иеротопия Scientists have determined the different cultural spaces sacred with very different, even contradictory
theoretical principles. Patrick Trusson displays sacred word of Indo-European root that determines compliance
space, the fundamental structure of things. The man always wants something stable, which protects against the
unexpected. Mircea Eliade emphasized that sacred higher than life. In Latin, the concept of sacred meaning
sacred thing dedicated to the gods. If a person has done something bad, then he is cut off from society. In
Christianity, describes the sacred religious sacrament, objects of worship. Analogues exists in other languages
such as Slavic and Indo-European concept of sacred means to increase. But there is another approach to the
concept of sacred when translated from German it means "rabble" and use it when they want to humiliate
someone. Several interpretations of sacred taboos associated with a violation of cosmic order. Etymology of the
sacred is not accidental contains the following contradiction, because its nature is manifested in action and
blasphemous holy, pure and impure. A detailed position of sacred can be represented by three positions. The
first position is based on religious experience, as sacred to feel. The second position supports the ability to learn
the language and sacred art. Thus it is necessary to use symbols. The third position is that the sacred can be
known through the scientific method as an objective reality by rational concepts and categories. Sacral
environment creates a wonderful feeling of merging with extraterrestrial creatures. Structuring space transforms
chaos into cosmos, aided by certain signs. Time is also regarded as sacred because of its return. The
contradictory notion of sacred projected on its etymology is no unanimity. It is proposed to distinguish the
interpretation of the sacred as a desire to tame chaos.
Keywords. Sacred, profanne, culture, sacral, hierotopy